Dislocation emission from the edge of a misfitting nanowire embedded in a free-standing nanolayer. (April 2019) - Mikaelyan, K.N.; Gutkin, M.Yu.; Borodin, E.N.; Romanov, A.E.
Abstract: Theoretical model is suggested which describes the misfit stress relaxation near a misfitting nanowire (NW) having the shape of a long parallelepiped embedded in a nanolayer. The stress relaxation is assumed to occur through the emission of dipoles of edge partial (or perfect) dislocations gliding along the NW face normal to the free surfaces of the nanolayer. The total energy change caused by the dislocation emission is calculated and analyzed in dependence on the distances passed by the dislocations. The energy barriers for the dislocation emission are determined and the equilibrium positions of the dislocations are calculated for different values of the system parameters. It is shown that this mechanism of stress relaxation is rather effective and should be taken into account in development of NW-related technology.